2010
DOI: 10.1177/1099800410375978
|View full text |Cite
|
Sign up to set email alerts
|

Antepartum Bed Rest for Pregnancy Complications: Efficacy and Safety for Preventing Preterm Birth

Abstract: Preterm birth is the major maternal-child health issue across developed nations and the leading cause of perinatal mortality and morbidity. Of all deaths of infants <1 year of age in the United States in 2005, 68.6% occurred in infants born prior to term. Although the preterm birth rate in European countries is 5-7%, the U.S. preterm birth rate is 12.7%, representing an increase of 9% since 2000. Antepartum bed rest/activity restriction (ABR/AR) has been a mainstay of treatment to prevent preterm birth for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
77
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(78 citation statements)
references
References 109 publications
(255 reference statements)
0
77
0
1
Order By: Relevance
“…Complications such as preeclampsia and premature labour may limit a woman from reaching term pregnancy and place her in a 'high-risk' category. Bed rest is a very common obstetrical management to restrict maternal activity even though there is minimal evidence that it decreases the risk of preterm delivery (Maloni, 2010). In addition Bigelow and Stone (2011) reviewed existing studies and found that there are no complications of pregnancy for which bed rest is consistently shown to be a beneficial intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Complications such as preeclampsia and premature labour may limit a woman from reaching term pregnancy and place her in a 'high-risk' category. Bed rest is a very common obstetrical management to restrict maternal activity even though there is minimal evidence that it decreases the risk of preterm delivery (Maloni, 2010). In addition Bigelow and Stone (2011) reviewed existing studies and found that there are no complications of pregnancy for which bed rest is consistently shown to be a beneficial intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Limited research evidence would suggest that pregnant women are also affected by the physiological effects of activity restriction. Important antepartum side effects range from loss of muscle strength and muscle atrophy, weight loss, dizziness, headaches and indigestion to possible lifethreatening thromboembolic events [10][11][12][13][14][15]. Bed rest may therefore be responsible for complicating the antepartum period, regardless of the disease process for which bed rest was originally prescribed.…”
Section: Introductionmentioning
confidence: 99%
“…Maternal stress is high during hospitalization, with the primary sources of stress as separation from and concerns for the family at home, negative emotions, self-image, and health status. [7][8][9] Bed rest may increase costs for the families, directly because of the expenses for the care of other children, or indirectly through job absenteeism. Lastly, it may also increase healthcare costs.…”
mentioning
confidence: 99%
“…1 In fact, there are increasing evidences that bed rest causes several adverse physiological and psychological side effects in women and their infants. 7 Some of these physiological and psychological side effects experienced in the antenatal period due to bed rest may develop when the individual cannot meet her own self-care needs sufficiently. When self-care is effectively performed, it helps to maintain structural integrity and human functioning and contributes to human development.…”
mentioning
confidence: 99%
See 1 more Smart Citation